Evaluating the efficacy of vestibular rehabilitation therapy on quality of life in persistent postural-perceptual dizziness: the role of anxiety and depression in treatment outcomes - Alahmari, Khalid A.; Alshehri, Sarah (Frontiers in Neurology, 2025)
BackgroundPersistent Postural-Perceptual Dizziness (PPPD) is a chronic disorder that significantly affects the quality of life (QoL) and daily living. Vestibular rehabilitation therapy (VRT) has emerged as a promising treatment option, yet its effectiveness, particularly in relation to symptom duration, anxiety, and depression, remains underexplored.MethodsThis cross-sectional study assessed the effect of VRT on the QoL in 188 PPPD patients, as well as the correlation between the duration of symptoms and dizziness severity and the role of anxiety and depression in the treatment response. QoL was assessed using the EuroQol-5 Dimension (EQ-5D), and dizziness-related handicap using the Dizziness Handicap Inventory (DHI) and anxiety and depression using the Hospital Anxiety and Depression Scale (HADS).ResultsNinety three patients were included in the analysis. QoL was significantly improved post-VRT with a greater mean EQ-5D score (EQ-5D post-VRT 0.72; EQ-5D pre-VRT 0.61, p = 0.032). Age was also found to correlate with increased dizziness severity (p < 0.001), although this was not as strong as the correlation of symptom duration (longer duration correlating with increased dizziness severity; p < 0.01), anxiety (r = −0.45, p = 0.002) and depression (r = −0.51, p < 0.001) (both significantly associated with poorer outcomes especially with reference to VRT) emerging as independent correlates of reduced effectiveness of treatment.ConclusionsThis study revealed the benefit of VRT in patients with PPPD on QoL and indicates the importance of identifying and treating psychological factors to improve the success of treatment for PPPD.